Java bytecode to Pilar translator - Ochani, Vidit (Kansas State University, 2013)
Software technology is the pivot around which all modern industries revolve. It is not surprising that industries of diverse nature such as finance, business, engineering, medicine, defense, etc. have assimilated sophisticated software in every step of functioning. Subsequently, with larger reach of application, software technology has evolved intricately; thereby thwarting the desirable testing of software. Companies are investing millions of dollars in manual and automated testing, however, software bugs continue to persist. It is well known that even a trivial bug can ultimately cost the company millions of dollars. Therefore, we need smarter tools to help eliminate bugs. Sireum is a research project to develop a software analysis platform that incorporates various tools and techniques. Symbolic execution, model checking, deductive reasoning and control flow graph are few examples of the aforementioned techniques. The Sireum platform is based on previous projects like the Indus static analysis framework, the Bogor model checking framework and the Bandera Java model checker. It uses the Pilar language as intermediate representation. Any language which can be translated to Pilar can be analyzed by Sireum. There exists translator for Spark - a verifiable subset of Ada for building high-integrity systems. In this report, we are presenting one such translator for Java Bytecode - A frontend which can generate Pilar from Java intermediate representation. The translator emulates the working of the Java Virtual Machine(JVM), by simulating a stack-based virtual machine. It will help us analyse JVM based softwares, such as, mobile applications for Android. We also evaluate and report statistics on the efficiency and speed of translation.
Keywords: Pilar; Translation; Sireum; Bytecode; Computer Science (0984)